A study of Rock Coast Erosion on the Atlantic coast of Ireland - CULLEN, NIAMH (Trinity College Dublin. School of Natural Sciences. Discipline of Geography, 2019)
The rate and processes of erosion on a coastal rock cliff on the west coast of Ireland are investigated. The links between site characteristics (wave climate, nearshore bathymetry, foreshore characteristics (platform roughness, elevation) and cliff and platform erosion are explored. This integrated approach gives new insights into controls on the spatial distribution of erosion on rock coasts. This is achieved through high resolution measurements of cliff and platform topography using Terrestrial Laser Scanning and Structure from Motion Photogrammetry respectively, empirical assessment of rock mass characteristics (discontinuities), wave modelling, and characterization of the nearshore and foreshore environment using Digital Elevation Models and topographic surveys.This work provides the following new insights: (1) The current rate of erosion at the study site is two orders of magnitude greater than previously estimated for Ireland's rock coastline. (2) Rock discontinuities exert a strong control on the rate and spatial distribution of erosion at the study site. (3) Nearshore bathymetry and foreshore characteristics have a strong influence of the alongshore distribution of wave energy available for erosion of the cliff. (4) Abrasion by clast transport is a geomorphologically significant process of platform erosion at the study site. (5) The type of abrasion feature observed is determined by the clast transport mode, which itself is strongly influenced by platform roughness. (6) Important links exist between cliff and platform erosion. (7) Cross scalar measurements of platform erosion using Structure from Motion Photogrammetry presents a significant opportunity for bridging the gap between micro and meso scale studies of platform erosion. The implication of this study is that integrated studies of rock mass, foreshore and nearshore characteristics are required to effectively explain the spatial variability of erosion on rock coasts
APPROVED
Keywords: Rock coasts; Cliffs; Shore platforms; Erosion; Remote sensing